2018
DOI: 10.3856/vol46-issue3-fulltext-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stocking densities in blood chemistry and biochemical body composition of Nile tilapia Oreochromis niloticus and the prawn Macrobrachium americanum in polyculture

Abstract: ABSTRACT. An assay on tilapia Oreochromis niloticus and freshwater prawn Macrobrachium americanum in polyculture was conducted during 112 days to study the effect on their blood chemistry and biochemical body composition to determine the feasibility of this polyculture in high density. Six densities were evaluated [T4/5, T9/5, T14/5, T0/5, T9/0, and T14/0; Ttilapia/prawn (ind m -2 )]. In tilapia were evaluated hemoglobin, red cells albumin, globulin, cholesterol, glucose, and triglycerides composition in bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In addition, cortisol level in L. vannamei fed commercial diet plus indigenous probiotic was not significantly different compared with control group. The fluctuation of albumin level reflects changes in nutritional, ecological and health status (Kovyrshina & Rudneva, 2012;Santamaria Miranda et al, 2018). Moreover, the concentration of albumin has identified as a good marker to determination of liver function and inflammation (MacQueen, Sadler, Walker, Wassif, & Evans, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, cortisol level in L. vannamei fed commercial diet plus indigenous probiotic was not significantly different compared with control group. The fluctuation of albumin level reflects changes in nutritional, ecological and health status (Kovyrshina & Rudneva, 2012;Santamaria Miranda et al, 2018). Moreover, the concentration of albumin has identified as a good marker to determination of liver function and inflammation (MacQueen, Sadler, Walker, Wassif, & Evans, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Research in crustacean biochemistry has developed in recent years, because it is useful for controlling health and nutritional condition of culture (Mercier et al, ; Pourmozaffar, Hajimoradloo, Paknejad, & Rameshi, ). A number of researchers evaluated biochemical variables in various conditions such as salinity stress (Lee & Chen, ), dietary regime (Zhao et al, ), stocking density (Santamaria Miranda et al, ) and different ecological place (Adeogun, Salami, Chukwuka, & Alaka, ). Therefore, the measuring of these indices is necessary to understand how shrimp health is affected by the internal physiological state and the external environment.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of stocking densities on blood chemistry and biochemical body composition of this prawn cultured and the Nile tilapia (Oreochromis niloticus) were evaluated by Santamaría-Miranda et al (2018). The results revealed that a combination of 14 fishes per five prawns produced similar growth compared to a monoculture, with no effect on blood or hemolymph chemistry and proximal composition on any species.…”
Section: Macrobrachium Americanummentioning
confidence: 99%